Economics of change in less developed countries - Colman, David; Nixson, F. I. (New York : Wiley, 1978)
The book draws together a wide range of views from different ideological standpoints about the causes, measurement and meaning of development. It pays special attention to the role of agricultural and rural development and the problem of structural inflation, and also discusses the importance of equality as a goal for developing countries.
"A Halsted Press book."
Includes bibliographical references and indexes.
oif 19/07/16
Loans
Keywords: Economic conditions; Economic development; Economic history; Developing countries